Development of a Novel Reverse Transcription Loop‐Mediated Isothermal Amplification Assay for the Rapid Detection of African Horse Sickness Virus. Issue 5 (2nd August 2016) - Fowler, V. L.; Howson, E. L. A.; Flannery, J.; Romito, M.; Lubisi, A.; Agüero, M.; Mertens, P.; Batten, C. A.; Warren, H. R.; Castillo‐Olivares, J.
Summary: African horse sickness (AHS) is a disease of equids caused by African Horse Sickness Virus (AHSV) and is transmitted by Culicoides midges. AHS is endemic in sub‐Saharan Africa, but during the past century, outbreaks of significant economic importance and elevated mortality have been recorded in Northern African countries, the Iberian and Arabian Peninsula, the Middle East and the Indian subcontinent. Effective control combines the application of early warning systems, accurate laboratory diagnosis and reporting, animal movement restrictions, suitable vaccination and surveillance programs, and the coordination of all these measures by efficient veterinary services. Conventional reverse‐transcriptase (RT) PCR (RT‐PCR) and real‐time RT‐PCR (rRT‐PCR) assays have improved the sensitivity and rapidity of diagnosing AHS, resulting in the adoption of these methods as recommended tests by the World Organisation for Animal Health (OIE). However, currently these assays are only performed within laboratory settings; therefore, the development of field diagnostics for AHS would improve the fast implementation of control policies. Loop‐mediated isothermal amplification (LAMP) is an isothermal, autocycling, strand‐displacement nucleic acid amplification technique which can be performed in the field. LAMP assays are attractive molecular assays because they are simple to use, rapid, portable and have sensitivity and specificity within the range of rRT‐PCR. This study describes the development of a novel RT‐LAMP assay for the detection of AHSV. The AHSV RT‐LAMP assay has an analytical sensitivity of 96.1% when considering an rRT‐PCR cut‐off value of C T  > 36, or 91.3% when no rRT‐PCR cut‐off is applied. Diagnostic sensitivity and specificity were 100%. This assay provides for a rapid and low cost AHS diagnostic for use in the field.